Cognitive Therapy for Social Anxiety Disorder: The Impact of the "Self-Focused Attention and Safety Behaviours Experiment" on the Course of Treatment. Issue 2 (March 2015) - Schreiber, Franziska; Heimlich, Christiane; Schweitzer, Clea; Stangier, Ulrich
<x content-type="archive" xml:space="preserve">Abstract</x> Background and Aims: Several studies have shown that cognitive therapy is an effective treatment for social anxiety disorder (SAD). However, it remains unclear which of the complex interventions are associated with an anxiety reduction during the course of treatment. The aim of this study was to examine the impact of the intervention referred to as the "self-focused attention and safety behaviours experiment" on treatment outcome. Method: This study was part of a randomized controlled trial including 16 sessions of either individual cognitive therapy (CT) or interpersonal therapy (IPT) for SAD. Of particular importance, a concomitant time-series analysis was used to investigate the impact of the self-focused attention and safety behaviours experiment on subsequent social anxiety (1, 2, 3, and 4 weeks after the intervention) in 32 patients with SAD, who are receiving cognitive treatment. Results: The results revealed a significant reduction of social anxiety after the self-focused attention and safety behaviours experiment during the subsequent month of treatment. Conclusion: The findings of the current study confirm current cognitive theories of SAD and demonstrate the importance of interventions that target self-focused attention and safety behaviour in cognitive therapy for SAD.